The Efficacy of Vibhithaki Ksharasutra in the Management of Nadivrana w.s.r Pilonidal Sinus (International Journal of Ayurveda and Pharma Research, 2024)
Pilonidal sinus (PNS) is a chronic disorder that occurs in the space between the buttocks (natal cleft). Men are more susceptible (because they have more hair) to pilonidal sinus than women. Excision, primary closure and reconstructive flap surgery are the most commonly used surgical techniques for this disease. However, there is a high risk of recurrence or wound infection after surgery. In addition, the patient needs a longer hospital stay, and the procedure is expensive. Acharya Susrutha (800 BC) considered this disease under Nadivrana (Shalyaja) and advocated a minimally invasive para surgical treatment namely the Kshara Sutra procedure. Susrutha mentioned Kshara dravyas like Apamarga, Palasha, Vasa, Vibhithaki, etc used in the preparation of the Ksharasutra. Here we selected Vibhitaki to prepare Kshara and Ksharasutra. Vibhithiki is cost-effective as it is easily available and the properties of this plant are favourable to Kshara qualities. The present case study deals with the efficacy of Vibhitaki Ksharasutra in the management of Nadivrana (pilonidal sinus).